DISPOSITION EFFECT TERHADAP HUBUNGAN ANTARA NILAI FUNDAMENTAL DAN HARGA SAHAM PADA PERIODE KRISIS FINANSIAL - Yohanes Indrayono (Jurnal Keuangan dan Perbankan, 2011)
Stock price was positively affected by a change of company fundamental value which included profitability,growth, and dividend factors. Excess volatility hypothesis, on the other hand, indicated that stock price wastoo volatile correlated to its fundamental value. This study empirically investigated the moderating impact ofdisposition effect - the tendency to sell stocks that had appreciated in price (winners) too soon and to hold stocksthat trade price below the purchase price (losers) too long - on the relationship between fundamental values andstock prices. Fifty-three stocks of Indonesian Stock Exchange were chosen as the research sample based onsampling criteria for the periods before, during, and after the 2008 financial crisis. By using multiple regressionsanalyses, this study revealed that during these periods, disposition effect weakened the positive relationshipbetween earning per share and stock prices as well as between book value per share and stock prices. Thehigher the proportion of disposition investors, the less sensitive the stock price to the changes in fundamentalvariables. Unlike previous studies that investigated the direct impact of disposition effects on stock prices, thisstudy investigated the indirect impact of disposition effect on stock prices. Thus, this study contributed to theexisting behavioral finance literature by providing some useful insights into understanding why stock priceswere less sensitive to the changes in fundamental variables in the presence of disposition effect.